The system of numeral classification in Cholon - Salas García, José Antonio (2012)
The objective of this piece of work is to present the system of numeral classification used in the language of the Cholons. First of all we have looked at the written sources for this study and then we decided on the morphosyntactic status of the terms of numeral classification. After this, by comparing the grammatical characteristics revealed by confronting them with the contexts in which they appear we managed to describe thee classifying terms and their functions in detail and place them in groups of semantic categories. Finally we noticed a classifying term in a language called Hibito which is obviously related to Cholon and then we made a critical study of a relationship between a Hibito-Cholon family and the Chibcha language.